Pengaruh Beberapa Faktor Strategis terhadap Indeks Pembangunan Manusia di Propinsi Nusa Tenggara Barat Periode 2015-2021 - Ida Bagus Eka Artika; Ida Ayu Ketut Marini; Irianto Irianto (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
The human development index as an indicator in measuring of the development of a country or a region reflects the improvement in the quality of human resources that must be achieved as a goal of sustainable development proclaimed by the United Nations Development Program. West Nusa Tenggara Province as one of the provinces in Indonesia with a human development index which is in the medium level category in 2021 (68,65), is still below the average national human development index (71,94, 2020 ). This is a research with documentation data collection method, aims to determine the effect of strategic variables that are components in measuring the human development index, namely poverty level, dependency ratio, average length of schooling and life expectancy of the population, during the period 2015 – 2021. The result show that the poverty rate and population dependency ratio have a negative effect on the human development index while the average length of schooling and life expectancy show a positive effect. The provincial government of West Nusa Tenggara, is expected to accelerate development programs, especially those strategic variables used to increase the achievement of the human development index.